Bracing for impact: The role of information science in supporting societal research impact. Issue 1 (2015) - Given, Lisa M.; Kelly, Wade; Willson, Rebekah
ABSTRACT: Academics are increasingly being asked to demonstrate the impact of their research beyond the walls of the academy. Societal impact measures were introduced as part of the Research Excellence Framework exercise in the UK in 2014 with a number of other countries, including Australia, considering similar assessments. As societal impact measures continue to proliferate there will be significant implications for academics, institutions, and academic libraries to document and support these activities. Information science is well‐placed not only to guide practical supports within our institutions, but also to develop metrics and qualitative approaches to assess this type of research impact. This exploratory qualitative study — situated in a constructivist grounded theory methodology — investigated academics' experiences and perceptions of the concept of societal research impact and the supports needed to facilitate this work. The definition of impact varied greatly among participants, but regardless of the participant's conception, interviewees felt that they were not prepared, trained, or had access to the needed supports to adequately document non‐academic types of impact. The data point to a number of emergent themes including a lack of relevant methodologies for tracking societal impact, the shortcomings of metrics approaches to document impact outside of academe, and the need for academic libraries to extend current reference and training supports to provide researchers with the tools and skills needed in this new impact landscape. Implications for research and development in information science related to scholarly communication, researchers' information behaviors, and impact measures are also explored.